2012
DOI: 10.1124/jpet.112.198358
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Anthracycline Cardiotoxicity: Molecular and Functional Analysis with Focus on Nuclear Factor Erythroid 2-Related Factor 2 and Mitochondrial Biogenesis Pathways

Abstract: Anthracycline anticancer drugs (e.g., doxorubicin or daunorubicin) can induce chronic cardiotoxicity and heart failure (HF), both of which are believed to be based on oxidative injury and mitochondrial damage. In this study, molecular and functional changes induced by chronic anthracycline treatment with progression into HF in post-treatment follow-up were analyzed with special emphasis on nuclear factor erythroid 2-related factor 2 (Nrf2) and peroxisome proliferator-activated receptor-␥ coactivator-1␣ (PGC1␣)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 49 publications
(57 reference statements)
1
33
0
1
Order By: Relevance
“…Issan et al (18) observed increased protein expression of HMOX1 after short anoxic (120 min, 100% argon exposure) stimulus, and overexpression of HMOX1 attenuated cardiomyocyte damage caused by an anoxic insult. Moreover, HMOX is often increased in the defense to cardiotoxic stimuli (23). Another iron-dependent antioxidant ACO1 displayed elevated mRNA levels under both protective regimens in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Issan et al (18) observed increased protein expression of HMOX1 after short anoxic (120 min, 100% argon exposure) stimulus, and overexpression of HMOX1 attenuated cardiomyocyte damage caused by an anoxic insult. Moreover, HMOX is often increased in the defense to cardiotoxic stimuli (23). Another iron-dependent antioxidant ACO1 displayed elevated mRNA levels under both protective regimens in our study.…”
Section: Discussionmentioning
confidence: 50%
“…40,41 The same was found in daunorubicin-treated male rabbits. 14 In the present study, PGC-1β seemed a relevant target of doxorubicin in males because its downregulation is also observed at the onset of cardiac toxicity. PGC-1β discovered a decade ago, is expressed predominantly in skeletal muscle, heart, brain, and brown adipose tissue.…”
Section: Discussionmentioning
confidence: 95%
“…However, the level and importance of oxidative stress are surely time, species, and concentration dependent leading to different results according to the model of doxorubicin treatment. 4,14,27,28,31,32 Cardiomyocyte loss through various cell death signaling pathways linked to oxidative stress and DNA damage and mitochondrial alterations has been described in doxorubicin cardiotoxicity. 28,33 However, depending on in vitro and in vivo analyses, the results were not always consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown doxorubicin to cause cardiotoxicity through the generation of free radicals [5], stimulation of lipid peroxidation [6] and alteration and disruption of cellular membrane integrity [7]. Arrhythmias, hypotension and depression of the contractile function are some of the acute effects of doxorubicin-induced cardiotoxicity [8], while chronic heart failure and dilative cardiomyopathy are more common and severe in patients who are on long term anthracyclines treatment [9,10]. Large scale clinical trials have shown that doxorubicin induced cardiotoxicity is irreversible and dose dependent [11].…”
Section: Introductionmentioning
confidence: 99%